Land Policy Instruments in Nepal - Chhetri, Ram Bhandari (Journal of the Institute of Engineering, 2014)
Corporate mobilization can be made realistic if policy facilitation is provided by the government sector. This research study aimed at exploring the possibility of a mechanism that will attract substantial investments from the private sector by mobilizing the existing capital market. To do so, the research within its objective framework examined the essential policy framework from the literature review, the existing legal, financial and planning and housing policies posing impediments to the prospective participation of the corporate sector in land and housing activities. This included but not necessarily restricted to the land administration, land legislatives, cadastral mapping system and current planning techniques used and the operational constraints it would pose upon the prospective mobilization of the corporate financing in land and housing development. The research study then finally intended to arrive at the framework that could possibly facilitate or promote corporate finance in land and housing sector in a greater way. The finding from the research is then translated into a framework for increased participation for corporate sector in land and housing that chiefly included following aspects. DOI: http://dx.doi.org/10.3126/jie.v10i1.10880 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 69–79